Graphene oxide effects on the properties of Al2O3-Cu/35W5Cr composite. (15th January 2020) - Zhang, Xiaohui; Zhang, Yi; Tian, Baohong; Jia, Yanlin; Fu, Ming; Liu, Yong; Song, Kexing; Volinsky, Alex. A.; Yang, Xiao; Sun, Hang
Abstract: Graphene oxide (GO) nanosheets were dispersed into premixed powders (Cu-0.4 wt% Al/35W5Cr) by wet grinding and vacuum freeze-drying process. The 0.3 wt% GO/Al2 O3 -Cu/35W5Cr and 0.5 wt%GO/Al2 O3 -Cu/35W5Cr composites, used for electrical contacts, were fabricated by vacuum hot-pressing sintering. The microstructure was analyzed by field emission scanning electron and transmission electron microscopy. In addition, the Raman spectroscopy and X-ray photoelectron spectroscopy were used to investigate the structural changes of GO before and after sintering. The arc erosion behavior was investigated by the JF04C electrical contact testing apparatus. Consequently, the Al2 O3 nanoparticles were evenly dispersed in the matrix, causing dislocation tangles. GO was converted to reduced graphene oxide after sintering. A group of carbon atoms combined with Cr forming Cr3 C2 in situ during sintering, which enhanced the interface bonding. Compared with the Al2 O3 -Cu/35W5Cr composite, the tensile strength of the two contact materials containing 0.3 wt% GO and 0.5 wt% GO was increased by 45% and 34%, respectively. Finally, pips and craters were present on the anode and cathode surfaces, respectively. Tungsten has undergone re-sintering during arcing and formed needle-like structures. Compared with Al2 O3 -Cu/35W5Cr, the GO/Al2 O3 -Cu35W5Cr composites have better welding resistance. The final mass transfer direction of the two composites was from the cathode to anode.